Application of a proteolysis/mass spectrometry method for investigating the effects of inhibitors on hydroxylase structure. - Stubbs, C; Loenarz, C; Mecinović, J; Yeoh, K; Hindley, N; Liénard, B; Sobott, F; Schofield, C; Flashman, E (2009)
Limited proteolysis coupled to matrix-assisted laser desorption/ionization (MALDI) mass spectrometric analyses can be used to screen for compounds that alter protein structure by monitoring stabilizing/destabilizing effects with respect to the rate and nature of proteolysis. When applied to prolyl hydroxylase 2, a key enzyme involved in human oxygen sensing, the method efficiently revealed differential effects on proteolytic stability for structurally similar compounds and for different substrates.